Walk the talk: Shareholders' soft engagement at annual general meetings - Alix Auzepy; Christina E. Bannier; Fabio Martin (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
The right to ask questions and voice their opinions at annual general meetings (AGMs) represents one of the few avenues for shareholders to communicate directly and publicly with the firm's management. Examining AGM transcripts of U.S. companies between 2007 and 2021, we find that shareholders actively express their concerns about environmental, social and governance (ESG) issues in accordance with their specific relationship with the company. Further, they are also demonstrably more vocal about ESG issues at AGMs of firms with poor sustainability performance. What is more, we show that this soft engagement translates into a more negative tone which, in turn, results in lower approval rates for management proposals. Shareholders' soft engagement at AGMs is hence an effective way to "walk the talk".
urn:nbn:de:hebis:30:3-681456
Keywords: G23; G34; G39; 330; shareholder engagement; annual general meeting; ESG; textual analysis